Fatigue strength of truck components in cast iron – Fatigue rig design, test results and analysis - Olsson, Anders (My University, 2011)
Fatigue properties of a two spherical graphite cast irons, (SGI), EN-GJS-500-14 and EN-GJS-500-7 in an as-cast truck component are evaluated. The examined component is a V-stay anchorage, and has a function of fixating the rear axle of a truck. The component is currently cast in the conventional SGI, EN-GJS-500-7. The matrix of EN-GJS-500-7 consists of a mixture of pearlite and ferrite. The mixture can vary within a component, depending on wall thickness and cooling time, leading to large variations in the hardness of the material. The newer SGI, EN-GJS-500-14, is solution strengthened with silicon and the matrix consists only of ferrite giving the material a more even hardness distribution. Large variation in hardness makes machining hard to optimize, which gives EN-GJS-500-14 an advantage in components requiring machining. To change materials in truck components, fatigue properties of the as-cast component is needed. The component is tested in a rig, designed so that the component experiences truck-like loading and boundary conditions. The stress response in the component, under truck-like conditions and rig conditions, is computed in FE analyses. Parameters affecting the stress response are identified and their influence evaluated in the analyses. Due to time limitations the fatigue testing is not completed before the publication of this report. Therefore, no conclusions about the fatigue strength of EN-GJS-500-14 are included in this report. The main contributions of the thesis are the design of a physical fatigue test rig and an evaluation of parametric influences from FE analyses. The results from the simulations have been used to build a physical rig where V-stay anchorages can be tested under truck-like conditions. Some test results are included in the report, but large parts of the test scheme have, as mentioned, not yet been performed.
Keywords: Materialvetenskap; Produktion; Transport; Hållbar utveckling; Innovation och entreprenörskap (nyttiggörande); Fastkroppsmekanik; Konstruktionsteknik; Funktionella material; Materials Science; Production; Transport; Sustainable Development; Innovation & Entrepreneurship; Solid mechanics; Construction engineering; Functional materials